The Computer Program Development to Determine The Shares of Inheritance for Three Types of Heir - Salmawaty Arif; Rahmi Muliana; Syarifah Meurah Yuni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Abstract: This research studied an Acehnese manuscript table about inheritance distribution. The purpose of the study was to create the general rules among the heir types in the table such that its share priorities were obtained. With the existence of these priorities, the relations among the portions were known which make it was possible to develop an algorithm and the computerized table for three types of the heir. This table consists of the shares for three types of an heir from the domain of ten types of heir selected in this research. The computer program was built by first determining the more important ones between the two related shares. From the total 120 cases investigated, four cases did not follow the developed priorities. The governing table for the three types of heir is expected to be the foundation to the determination of the shares for three types of the heir.Abstrak: Penelitian ini mengkaji isi sebuah tabel manuskrip Aceh tentang pembagian warisan sehingga didapatkan suatu ketentuan umum tentang prioritas dari bagian-bagian warisan tersebut. Dengan adanya prioritas ini, diperoleh suatu hubungan antar bagian warisan sehingga dapat dibangun suatu algoritma untuk komputerisasi tabel bagian tiga jenis ahli waris. Tabel ini berisi bagian tiga jenis ahli waris dari sepuluh jenis ahli waris yang dipilih sebagai domain. Program komputer ini dibangun dengan menentukan bagian yang lebih diprioritaskan di antara dua bagian. Dari total 120 kasus, terdapat empat kasus yang tidak mengikuti prioritas yang telah dibangun. Hasil berupa tabel tiga jenis ahli waris ini diharapkan menjadi dasar untuk penentuan tiga jenis ahli waris dari seluruh jenis ahli waris yang berjumlah 30 tersebut.